1993
DOI: 10.1212/wnl.43.3_part_1.537
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose intravenous immunoglobulin therapy in multifocal motor neuropathy

Abstract: Article abstract-We treated five consecutive patients with multifocal motor neuropathy (MMN) with high-dose intravenous immunoglobulin (IVIg). Four patients had increased levels of anti-asialo-GM, IgM and two of anti-GM, IgM as well; one patient had no reactivity. We treated them twice with 0.4 g/kg IVIg for 5 consecutive days at a 2-month interval, followed by maintenance infusions up to 6 to 12 months. All patients with high anti-asialo-GM, had a consistent clinical improvement starting 3 to 10 days after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 27 publications
2
94
0
2
Order By: Relevance
“…Patients were asked about current status, subjective improvement in symptoms, associated medical conditions and current therapy. The overall level of walking disability was assessed by a functional impairment scale used previously to assess leg function in patients with chronic peripheral neuropathy and adapted for telephone interviews [18, 19]: 0 = asymptomatic; 1 = mild symptoms not interfering with normal walking; 2 = walking abnormally but without support; 3 = walking independently with the support of one stick; 4 = needing help to walk [two sticks, walking frame or person(s) to support], and 5 = wheelchair bound. A score of ≤2 was considered good functioning.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were asked about current status, subjective improvement in symptoms, associated medical conditions and current therapy. The overall level of walking disability was assessed by a functional impairment scale used previously to assess leg function in patients with chronic peripheral neuropathy and adapted for telephone interviews [18, 19]: 0 = asymptomatic; 1 = mild symptoms not interfering with normal walking; 2 = walking abnormally but without support; 3 = walking independently with the support of one stick; 4 = needing help to walk [two sticks, walking frame or person(s) to support], and 5 = wheelchair bound. A score of ≤2 was considered good functioning.…”
Section: Methodsmentioning
confidence: 99%
“…In the second condition, the increased range of conduction velocities may lead to an increased duration of the proximally stimulated CMAP (abnormal temporal dispersion) that may result itself in a reduced CMAP amplitude. Other authors use more stringent criteria to better distinguish true PMCB from the reduction of CMAP amplitude sometimes seen in chronic demyelination and 599 in chronic axonal loss, and consider a reduction of the proximal to distal CMAP amplitude or area of more than 40%14 16 …”
Section: Electrophysiological Featuresmentioning
confidence: 99%
“…Two retrospective studies on the natural course of MMN have been published; both reported a slowly progressive course. 22,32 Step-wise 31,55 and spontaneously remitting 2,19 disease courses have also been described but are less common than the slow progressive course. In a study of 38 patients with MMN, we 32 showed that disease duration and disease severity are related.…”
Section: Natural Coursementioning
confidence: 99%